2020
DOI: 10.1093/cid/ciaa624
|View full text |Cite
|
Sign up to set email alerts
|

Association of Renin-angiotensin-aldosterone System Inhibitors With Coronavirus Disease 2019 (COVID-19)- Related Outcomes in Korea: A Nationwide Population-based Cohort Study

Abstract: Background Renin-angiotensin-aldosterone system (RAAS) inhibitors may facilitate host cell entry of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) or attenuate organ injury via RAAS blockade. We aimed to assess the associations between prior use of RAAS inhibitors and clinical outcomes among Korean patients with coronavirus 2019 (COVID-19). Methods We performed a nationwide population-based cohort study using th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
121
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(127 citation statements)
references
References 38 publications
5
121
1
Order By: Relevance
“…This indicates that there at least does not seem to be evidence of harm in ACEI/ARB usage among COVID-19 patients. In the 4 studies [26,27,33,34,37] where the unadjusted data showed a higher rate of mortality or severe disease, only the study by Selcuk et al, showed potential harm after adjustment for potential confounders [26]. However, it should be noted that this study had a small sample size of 113 patients hence, only a limited number of variables could be included in the regression model (not even gender and race were included) and other potential unknown confounders cannot be accounted for.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…This indicates that there at least does not seem to be evidence of harm in ACEI/ARB usage among COVID-19 patients. In the 4 studies [26,27,33,34,37] where the unadjusted data showed a higher rate of mortality or severe disease, only the study by Selcuk et al, showed potential harm after adjustment for potential confounders [26]. However, it should be noted that this study had a small sample size of 113 patients hence, only a limited number of variables could be included in the regression model (not even gender and race were included) and other potential unknown confounders cannot be accounted for.…”
Section: Discussionmentioning
confidence: 84%
“…A total of 21 studies were included in the final meta-analysis [2,7,[19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37]. Majority of the studies included had low to serious risk of bias in relation to the specific focus which was ACEI/ARB use and clinical outcomes, but no studies included had critical risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…The characteristics of the shortlisted studies are summarized in Table 1. Among shortlisted studies, 23 studies were from China , nine studies were from Italy [64][65][66][67][68][69][70][71][72], ten studies were from the United States [83][84][85][86][87][88][89][90][91][92], four studies were from South Korea [75][76][77][78], three studies were from France [60][61][62], two studies were from Spain [79,80], one study each was from Belgium [35], Denmark [59], Hong Kong [63], Kuwait [73], Singapore [74], Turkey [81], and the United Kingdom [82]; and one study included data from 38 countries [93]. There were 24 studies that included hypertensive patients exclusively (100%) [36, 38, 39, 43-45, 47, 48, 50-52, 54, 56, 58, 66, 71, 72, 75, 78, 81, 87-89, 91].…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…Since Selçuk et al [81] provided mortality estimates with a very wide CI (OR = 3.66; 95% CI 1.11-18.18), we excluded this study from our meta-analysis. In a pooled analysis of the 12 remaining original studies that provided adjusted ORs, with 18,749 COVID-19 patients being analyzed [35,64,66,75,76,78,80,86,88,89,92,93], the use of an ACEI/ARB was significantly associated with lower odds of mortality compared to non-use of an ACEI/ARB ( Fig. 2; pooled OR = 0.73, 95% CI 0.56-0.95).…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation